1979
DOI: 10.2190/6dx0-961a-6xjp-jaag
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Related to the Incidence of Cancer

Abstract: The recent data concerning the relationship between psychosocial factors and the incidence of cancer have been reviewed covering life events, personality factors, psychiatric diagnoses, and loss-separation-hopelessness. The multiple methodological and design problems in this area of investigation are the factors that stand out and make interpretation difficult. Nevertheless, an association between oncogenesis and a number of factors such as extraversion, neuroticism, and lack of closeness to family is suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…During the last few years'; cancer has often been mentioned as a disease in which stress could be a pathogenetic factor [16], Both experimental and epidemiological evidence supports this hypothesis [1,13], Sklar & Anisman [15] showed that stressed mice developed macroscopicaliy visible tumours before controls, after transplantation of cancer cells. Some of the observed differences may be due to a stress-induced alteration of the immune system.…”
mentioning
confidence: 97%
“…During the last few years'; cancer has often been mentioned as a disease in which stress could be a pathogenetic factor [16], Both experimental and epidemiological evidence supports this hypothesis [1,13], Sklar & Anisman [15] showed that stressed mice developed macroscopicaliy visible tumours before controls, after transplantation of cancer cells. Some of the observed differences may be due to a stress-induced alteration of the immune system.…”
mentioning
confidence: 97%
“…We are now aware that emotional stress down-regulates the immune system and makes people more prone to cancer [139-142]. Reich's analysis of the subtle energetic processes in cancer patients and their relationship to those emotional blocks makes his research perhaps the most original and intriguing area of study in the history of 20 th century medical science.…”
Section: Subtle Energetic Properties Of Nutrientsmentioning
confidence: 99%
“…Two other approaches to determining systematic differences in personality between cancer patients and other people will be mentioned only in passing, for lack of space and lack of convincing results issuing from them. There have been methodological difficulties, pointed out by Fox (1978) and Scurry and Levin (1978), in attempting to correlate mental disorders with cancer incidence, although the latter authors conclude that there is some evidence supporting lowered cancer mortality among schizophrenics and an increased risk among depressives. Secondly, there is a long history of psychoanalytic study and speculation on cancer and mind (Bahnson, 1969, 1981; Goldberg, 1981; Murray, 1980).…”
Section: Effects Of Psychological Factors On Cancermentioning
confidence: 99%
“…With the emergence of a more materialistic and technically oriented medicine in the 20th century, this aspect of cancer patho genesis fell into disrepute. However, interest in a possible mind/cancer link has revived over the last 30 years or so and seems to have grown even more rapidly during the last five or six (reviewed by Bahnson, 1980, 1981; Fox, 1978, 1983; Greer, 1979; Greer & Silberfarb, 1982; Holden, 1978; Scurry & Levin, 1979; Wellisch & Yager, 1983). In part, this resurgence of interest may have been stimulated by an increasing appreciation of the multifactorial causation of disease (Engel, 1977).…”
mentioning
confidence: 99%